Demelza - Graham, Winston (Naperville, Illinois Sourcebooks Landmark, 2015)
Demelza Carne, the miner's daughter Ross Poldark rescued from a fairground rabble, is now his wife. But the events of these turbulent years will test their marriage and their love. Ross begins a bitter struggle for the rights of the mining communities -- and sows the seed of an enduring enmity with powerful George Warleggan.
Keywords: Poldark, Ross (Fictitious character) -- Fiction; Married people -- Fiction; Cornwall (England : County) -- Fiction; Historical fiction; Love stories; Romance fiction